Transcranial direct current stimulation reduces injury potential but does not enhance performance during side-cutting among individuals with chronic ankle instability - Gao, He; Huang, Xueke; Song, Qipeng; Liu, Yanhao; Shen, Peixin; Wang, Qi; Zhao, Liang (Frontiers in Physiology, 2025)
BackgroundIndividuals with Chronic Ankle Instability (CAI) exhibit increased injury potential and impaired movement performance, which may be associated with adaptations in the central nervous system (CNS). However, conventional CAI rehabilitation primarily concentrates on peripheral interventions, with limited emphasis on CNS-targeted therapies. Research has shown that transcranial direct current stimulation (tDCS) is a CNS intervention with the potential to improve functional deficits among individuals with CAI. This study aims to investigate the additional effects of concurrent tDCS based on Bosu ball training (BBT) on injury potential and movement performance during side-cutting among individuals with CAI.MethodsForty participants with CAI were recruited and randomly divided into two groups, and received the tDCS + BBT or BBT interventions for 6 weeks, with three 20-min sessions per week. Before and after the intervention, kinematic and kinetic data during side-cutting were measured using a twelve-camera motion capture system and a force plate. Two-way ANOVA with repeated measures was used to analyze data.ResultsSignificant group-by-intervention interactions were detected in the ankle maximum inversion (p = 0.018, η2p = 0.162) and internal rotation (p = 0.023, η2p = 0.151) angles, they decreased in both groups from week 0 to week 7, and the changes were greater in the tDCS + BBT group compared to the BBT group. Significant main effects of the intervention were shown in the take-off velocity (p = 0.002, η2p = 0.271), jumping displacement (p < 0.001, η2p = 0.478), and push-off impulse (p < 0.001, η2p = 0.770), they increased in both groups from week 0 to week 7.ConclusionConcurrent tDCS based on BBT intervention has additional effects in reducing injury potential but not in enhancing movement performance during side-cutting among individuals with CAI. Our study provides new insights for clinically reducing the injury potential among individuals with CAI.